Pan-cancer analysis identifies olfactory receptor family 7 subfamily A member 5 as a potential biomarker for glioma - Bao, Yanqiu; Tang, Ziqi; Chen, Renli; Yu, Xuebin; Qi, Xuchen (PeerJ, 2024)
Background Human olfactory receptors (ORs) account for approximately 60% of all human G protein-coupled receptors. The functions of ORs extend beyond olfactory perception and have garnered significant attention in tumor biology. However, a comprehensive pan-cancer analysis of ORs in human cancers is lacking. Methods Using data from public databases, such as HPA, TCGA, GEO, GTEx, TIMER2, TISDB, UALCAN, GEPIA2, and GSCA, this study investigated the role of olfactory receptor family 7 subfamily A member 5 (OR7A5) in various cancers. Functional analysis of OR7A5 in LGG and GBM was performed using the CGGA database. Molecular and cellular experiments were performed to validate the expression and biological function of OR7A5 in gliomas. Results The results revealed heightened OR7A5 expression in certain tumors, correlating with the expression levels of immune checkpoints and immune infiltration. In patients with gliomas, the expression levels of OR7A5 were closely associated with adverse prognosis, 1p/19p co-deletion status, and wild-type IDH status. Finally, in vitro experiments confirmed the inhibitory effect of OR7A5 knockdown on the proliferative capacity of glioma cells and on the expression levels of proteins related to lipid metabolism. Conclusion This study establishes OR7A5 as a novel biomarker, potentially offering a novel therapeutic target for gliomas.
Keywords: OR7A5; Glioma; Olfactory receptors; Prognosis; Biomarker